A Novel ATP1A2 Gene Variant Associated With Pure Sporadic Hemiplegic Migraine Improved After Patent Foramen Ovale Closure: A Case Report - Perrotta, Armando; Gambardella, Stefano; Ambrosini, Anna; Anastasio, Maria Grazia; Albano, Veronica; Fornai, Francesco; Pierelli, Francesco (Frontiers in Neurology, 2018)
We describe the case of one patient with pure sporadic hemiplegic migraine (SHM) with a novel ATP1A2 gene variant and a large patent foramen ovale (PFO) with atrial septal aneurysm. In hemiplegic migraine (HM), the relationship between incomplete penetrance, environmental triggers and phenotypic expression is underdetermined. A genetic evaluation of the proband was requested for the HM associated genes and extended to the members of his family. Genetic analysis revealed a never described before ATP1A2 gene mutation, inherited by his father, who never experienced motor aura but only typical visual aura. The proband – but not his father - was also affected by a large PFO with atrial septal aneurysm. SHM patient showed a marked reduction in motor aura episodes per year in the twelve months following the PFO percutaneous closure, followed by a complete remission from attacks at least in the following twenty-four months. We speculated that as well as incomplete penetrance of the novel mutation and natural history of the disease, an additional pathological condition such as the PFO could contribute to the phenotypical expression in this case of HM.